2014
DOI: 10.1186/1477-7819-12-396
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse filiform polyposis of the small intestine without inflammatory bowel disease

Abstract: Filiform polyposis is a rare disease, which typically occurs in patients with inflammatory bowel disease. We report a case of filiform polyposis occurring in a 56-year-old man with no history or evidence of inflammatory bowel disease. The patient’s main symptoms were melena and anemia. We performed an emergency exploratory laparotomy, in which we observed worm-like polyps spread almost along the entire small intestine, and a partial resection of the small intestine to treat bleeding in the bowel was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The exact pathogenesis of FP is uncertain. It is likely that, long-standing inflammation of the colonic mucosa in chronic inflammatory bowel disease with alternating mucosal damage and healing may lead to exuberant mucosal regeneration giving rise to the mentioned unique appearance in FP [4,6]. In the present case, long standing ulcerative colitis with poor response to medical treatment, resulting in frequent relapses, might have contributed to FP.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The exact pathogenesis of FP is uncertain. It is likely that, long-standing inflammation of the colonic mucosa in chronic inflammatory bowel disease with alternating mucosal damage and healing may lead to exuberant mucosal regeneration giving rise to the mentioned unique appearance in FP [4,6]. In the present case, long standing ulcerative colitis with poor response to medical treatment, resulting in frequent relapses, might have contributed to FP.…”
Section: Discussionmentioning
confidence: 73%
“…However, patients may present with a variety of symptoms, including cramping abdominal pain, anaemia, weight loss, malena and diarrhoea. The condition can also produce obstruction and intussusception, especially in localized large fungating mass lesions as in this case [4].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been suggested that the continuous inflammatory process and the alternating periods of ulceration and healing may lead to the formation of finger-like projections [15]. To the best of our knowledge, 22 similar cases of filiform polyposis in patients without a history of inflammatory bowel disease (7 women, 15 men) have been reported at the time of writing [16]. Filiform polyposis may be sequelae of prior injury or inflammation and has been reported to be associated with necrotizing enterocolitis, enema-induced colitis, ureterosigmoidostomy, stercoral ulcer, Langerhans cell histiocytosis X, or colonic tuberculosis [11].…”
Section: Discussionmentioning
confidence: 85%